Association of Virological Response to Antiviral Therapy With Survival in Intermediate-Stage Hepatitis B Virus-Related Hepatocellular Carcinoma After Chemoembolization - Jin, Meng; Chen, Yong; Hu, Shuifang; Zhu, Meiyan; Wang, Yan; Chen, Minshan; Peng, Zhenwei (Frontiers in Oncology, 2021)
Introduction Role of response to antiviral therapies on survival of patients with intermediate-stage hepatitis B virus-related hepatocellular carcinoma (HBV-HCC) undergoing transarterial chemoembolization (TACE) remains unknown. We aimed to determine whether virological response (VR) or prolonged maintained virological response (MVR) to nucelos(t)ide analogues (NA) therapy could result in improved survival in HBV-HCC patients receiving TACE. Methods Between January 2012 and October 2018, data of patients with intermediate HBV-HCC who underwent TACE and started NA therapy within one week prior to TACE treatment at our institution were reviewed. Overall survival (OS) was compared using the Kaplan-Meier method with log-rank test between different VR status groups. Univariable and multivariable Cox regression analyses were used to determine the association between achievement of VR or MVR and OS. VR was defined as an undetectable HBV DNA level (<100 IU/ml) on two consecutive measurements during NA treatment. MVR was defined as a persistently undetectable HBV DNA level after achieving a VR. Results A total of 1265 patients undergoing TACE with a median follow-up time of 18 months (range, 2-78 months) were included in the analysis. Of 1265 NA-treated patients [1123 (88.8%) male, median (range) age, 56 (18-75) years], 744 patients (58.8%) achieved VR and the remaining patients (41.2%) did not. Patients with achievement of VR showed a significantly longer OS than those without VR (median OS: 21 vs 16 months; HR, 0.707; 95% CI, 0.622-0.804; P<0.001). Among patients with VR, MVR was present in 542 patients (72.8%), while the other 202 patients (27.2%) in the non-MVR group. The OS for the MVR group was significantly higher than the non-MVR group (median OS: 23.2 vs 18 months; HR, 0.736; 95% CI, 0.612-0.885; P=0.001). Additionally, patients with MVR status more than two years showed a better OS than those with just one-year (HR, 0.719; 95% CI, 0.650-0.797; P<0.001) or one-to-two-year MVR (HR, 0.612; 95% CI, 0.471-0.795; P=0.024). On multivariable analyses, splenomegaly and up-to-seven criteria were independent prognostic factors of OS in both VR and MVR cohorts. Conclusions In patients with intermediate-stage HBV-HCC, both VR to antiviral therapy and prolonged response are associated with prolonged OS after TACE, especially for those within up-to-seven criteria.